Dispersible porous classical polymer photocatalysts for visible light-mediated production of pharmaceutically relevant compounds in multiple solvents. Issue 3 (17th December 2019) - Ferguson, Calum T. J.; Huber, Niklas; Kuckhoff, Thomas; Zhang, Kai A. I.; Landfester, Katharina
Abstract : Porous classical polymer photocatalyst produced by RAFT mediated PISA, easily dispersible in a broad range of solvents for drug synthesis. Abstract : The dispersibility of photocatalytic polymeric materials is currently a limiting factor for wide scale use. Indeed, the dispersibility of photocatalytic material in solvents dictates its use as heterogenous catalysts, due in part to reagent solubility. Here, we describe a new platform for producing porous polymer photocatalytic nanoparticles that are easily dispersible in a broad range of solvents. Photocatalytic porous classical polymer nanoparticles have been designed, based on classical porous nanoparticles copolymerised with photocatalytic moieties. The combination of both classical and photocatalytic monomers results in an affordable highly photocatalytically effective material, that can be easily dispersed in a wide range of solvents. The versatility and useability of this new material has been demonstrated by photocatalysing a number of pharmaceutically relevant compounds in solvents with varying polarity.